Friction-Driven Membrane Scission by the Human Escrt-Iii Proteins chmp1b and ist1 - Castillo-Gutierrez, J (NATL ACAD SCIENCES, 2022)
The endosomal sorting complexes required for transport (ESCRT) system is an ancient and ubiquitous membrane scission machinery that catalyzes the budding and scission of membranes. ESCRT-mediated scission events, exemplified by those involved in the budding of HIV-1, are usually directed away from the cytosol ("reverse topology"), but they can also be directed toward the cytosol ("normal topology"). The ESCRT-III subunits CHMP1B and IST1 can coat and constrict positively curved membrane tubes, suggesting that these subunits could catalyze normal topology membrane severing. CHMP1B and IST1 bind and recruit the microtubule-severing AAA+ ATPase spastin, a close relative of VPS4, suggesting that spastin could have a VPS4-like role in normal-topology membrane scission. Here, we reconstituted the process in vitro using membrane nanotubes pulled from giant unilamellar vesicles using an optical trap in order to determine whether CHMP1B and IST1 are capable of membrane severing on their own or in concert with VPS4 or spastin. CHMP1B and IST1 copolymerize on membrane nanotubes, forming stable scaffolds that constrict the tubes, but do not, on their own, lead to scission. However, CHMP1B-IST1 scaffolded tubes were severed when an additional extensional force was applied, consistent with a friction-driven scission mechanism. We found that spastin colocalized with CHMP1B-enriched sites but did not disassemble the CHMP1B-IST1 coat from the membrane. VPS4 resolubilized CHMP1B and IST1 without leading to scission. These observations show that the CHMP1B-IST1 ESCRT-III combination is capable of severing membranes by a friction-driven mechanism that is independent of VPS4 and spastin.